Changes in Coalition Patterns of Ideological Political Parties to Transactional Pragmatists President Joko Widodo's Leadership Period 2014-2024 - Amsori, Amsori; Yuswarni, Yuswarni; Yandra, Alexsander; Aryanto, Aryanto; Karim, Muqaddim; Arizal, Arizal (Universitas Muhammadiyah Ponorogo, 2024)
This study discusses changes in the coalition pattern of political parties in the leadership period of President Joko Widodo who was elected in 2014 and 2019, this research uses a descriptive qualitative method with a literature/literature study approach, so the results show that in the first period the coalition pattern that was built was an ideological coalition pattern, but this pattern changed to transactional pragmatism, because the Coalition of political parties pro-president Joko Widodo's government experienced successive defeats in parliament, One of the defeats did not get a leadership seat in parliament because it lost the number of votes in parliament, so the ideological coalition pattern turned into a transactional pragmatic coalition, where President Joko Widodo attracted opposition parties, namely PPP, Golkar and PAN, to join the pro-government coalition, by sharing ministerial seats, with the aim that the government coalition could win in parliament in determining policies. In the second period of Joko Widodo's presidency, he became more pragmatic because Prabowo, who was Joko Widodo's rival, was drawn into a coalition with the government by giving Prabowo the position of Minister of Defense, so that the impact caused by democracy became unstable, because opposition parties were getting weaker and many policies in their determination were controversial, including the Job Creation Law, revision of the KPK Law, the IKN Law and the dissolution of organizations considered radical by the government.